Pendidikan Islam Holistik Komprehensif - Azzahra, Radhita; Annur, Saipul; Handayani, Tutut (Peneliti.net, 2025)
Holistic Comprehensive Islamic Education emphasizes a balanced approach to nurturing students intellectually, morally, spiritually, and physically. This method integrates religious values into the curriculum, aiming to produce individuals who are not only academically competent but also possess strong character and spiritual awareness. Rooted in the teachings of the Qur'an and Sunnah, holistic education offers solutions to modern challenges such as globalization while preserving Islamic identity. It also supports character development and contributes to educational policies by prioritizing moral and spiritual growth alongside intellectual achievements. This article explores the concept, foundations, and relevance of holistic comprehensive education in modern Islamic contexts. Using library research methods, the study analyzes theories from various experts to highlight the importance of integrating cognitive, affective, and psychomotor aspects in education. Examples include character education programs in Indonesia, such as collective prayer sessions and Quranic studies, which demonstrate effective implementation of holistic approaches. Nations like Malaysia and Turkey also adopt similar strategies tailored to their cultural contexts. Ultimately, holistic comprehensive Islamic education serves as a strategic solution for fostering balanced individuals who are intellectually capable, morally upright, and spiritually aware..